1995
DOI: 10.1080/00103629509369304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of green manure and lime on the growth of sweet corn and chemical properties of an acid Oxisol in western Samoa

Abstract: Liming values of calcium carbonate (CaCO3) and cowpea green manure were evaluated on an acid Oxisol (Typic Acrorthox, Togitogiga series), based on seed yield and tissue composition of sweet corn (Zea mays), and soil chemical properties. Application rates were 0, 5, and 10 Mg/ha for CaCO 3 and 0, 7.5, and 15 Mg/ha for the green manure, factorially arranged. Treatments with commercial NPK fertilizers were included for comparison. Growth and yield of sweet corn showed that soil acidity can be corrected by either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…De acordo com Hunter et al (1995), a baixa fertilidade de um solo ácido pode ser corrigida tanto pela calagem quanto pela adição do adubo verde, especialmente em solos de cargas dependentes do pH.…”
Section: Introductionunclassified
“…De acordo com Hunter et al (1995), a baixa fertilidade de um solo ácido pode ser corrigida tanto pela calagem quanto pela adição do adubo verde, especialmente em solos de cargas dependentes do pH.…”
Section: Introductionunclassified
“…Collar girth and leaf count of the potato accounted for 80. Hunter et al (1995) and Dhakal et al (2011) reported that application of plant biomass (foliage) and growing of trees in association with crops do bring about soil fertility improvement through soil moisture conservation and increase in nitrogen and organic matter status.…”
Section: Resultsmentioning
confidence: 99%
“…belongs to the family Leguminosae and subfamily Mimosaceae. It is a nitrogen fixing tree and its green manure when incorporated into the soil brings about reasonable soil improvement and enhances crop yield (Hunter et al 1995, Kareem 2008. Irish potato (Solanum tuberosum L.) was said to have originated from the Alti plano around the Lake Titicaca at an altitude of about 3000 m in the Bolivian Andes (Burton 1966, Kay 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados de pesquisas indicaram o grande potencial dos adubos verdes no fornecimento de nutrientes às culturas consorciadas (PERIN et al, 2004) e efeito favorável desta prática sobre características químicas do solo (HUNTER et al, 1995;OLIVEIRA, 1994) e rendimento das culturas BORTOLINI et al, 2000;HEINRISCHS et al, 2001). No entanto, apesar dos grandes avanços científicos, principalmente na última década, no sentido de identificar os adubos verdes mais adequados à inclusão nos sistemas de produção, a compatibilização de seu cultivo na mesma área de culturas comerciais constitui-se ainda uma das principais limitações de seu uso pelos produtores (AMABILE, 1996;SKÓRA NETO, 1993), apontando a consorciação como Ciênc.…”
Section: (Recebido Em 10 De Janeiro De 2006 E Aprovado Em 18 De Abrilunclassified